2015
DOI: 10.1519/jsc.0000000000000861
|View full text |Cite
|
Sign up to set email alerts
|

Fitness and Anthropometric Profiles of International vs. National Judo Medalists in Half-Heavyweight Category

Abstract: The aim of the study was to determine the anthropometric and fitness profiles of European half-heavyweight judokas by success in competition. For this purpose, we compared 5 international medalists (elite) with 5 national medalists (subelite). All male judokas won at least 1 medal in the half-heavyweight category during the previous 2 years. The testing in this cross-sectional study was performed during 4 days. All subjects underwent anthropometric assessment with body mass, height, skinfold, and limb circumfe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

5
96
5
2

Year Published

2016
2016
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 64 publications
(108 citation statements)
references
References 20 publications
5
96
5
2
Order By: Relevance
“…According to studies of Franchini, Takito, Kiss, and Sterkowicz (2005) and Classens, Beunen, Wellens, and Geldof (1987), elite judokas compared to non-elite judokas had a higher circumference of flexed arm, forearm, wrist and medial calf and breadths of humerus and femur epicondyles. In a recent study, Drid et al (2015) also confirmed significant differences in some morphological variables in elite groups of judo athletes (European and World medallist) compared to non-elite (only national medallist) groups. Moreover, elite judokas seem to have higher arm muscle mass than sub-elite athletes, but a similar body fat percentage.…”
Section: Introductionmentioning
confidence: 56%
“…According to studies of Franchini, Takito, Kiss, and Sterkowicz (2005) and Classens, Beunen, Wellens, and Geldof (1987), elite judokas compared to non-elite judokas had a higher circumference of flexed arm, forearm, wrist and medial calf and breadths of humerus and femur epicondyles. In a recent study, Drid et al (2015) also confirmed significant differences in some morphological variables in elite groups of judo athletes (European and World medallist) compared to non-elite (only national medallist) groups. Moreover, elite judokas seem to have higher arm muscle mass than sub-elite athletes, but a similar body fat percentage.…”
Section: Introductionmentioning
confidence: 56%
“…In literature, there are various studies assessing HGS values in different sports of elite and non-elite [11,16,17], elite and sub-elite athletes [18] and individuals doing sports and individuals doing no sports [8]. We found different studies on the evaluation of HGS of male Olympic style weightlifting athletes [19,20].…”
Section: Introductionmentioning
confidence: 99%
“…Anthropometric characteristics and body composition of male athletes practicing judo have been extensively studied with regard to age, weight categories, sporting experience and competitive level [9,12,13,18,20,31,35,37].…”
Section: Introductionmentioning
confidence: 99%